2010
DOI: 10.1074/jbc.m110.135541
|View full text |Cite
|
Sign up to set email alerts
|

Allostery Is an Intrinsic Property of the Protease Domain of DegS

Abstract: DegS is a periplasmic Escherichia coli protease, which functions as a trimer to catalyze the initial rate-limiting step in a proteolytic cascade that ultimately activates transcription of stress response genes in the cytoplasm. Each DegS subunit consists of a protease domain and a PDZ domain. During protein folding stress, DegS is allosterically activated by peptides exposed in misfolded outer membrane porins, which bind to the PDZ domain and stabilize the active protease. Proteases are carefully regulated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(87 citation statements)
references
References 24 publications
6
80
1
Order By: Relevance
“…Recent structural studies indicate that the binding of a C-terminal peptide from an outer membrane protein to the PDZ domain relieves inhibitory contacts between the PDZ and protease domains, thereby activating the protease domain (138). Interestingly, this allosteric activation seems to be an intrinsic property of the protease domain, as protein substrates must bind tightly and specifically to this domain to facilitate their own degradation (51,137).…”
Section: Degsmentioning
confidence: 99%
“…Recent structural studies indicate that the binding of a C-terminal peptide from an outer membrane protein to the PDZ domain relieves inhibitory contacts between the PDZ and protease domains, thereby activating the protease domain (138). Interestingly, this allosteric activation seems to be an intrinsic property of the protease domain, as protein substrates must bind tightly and specifically to this domain to facilitate their own degradation (51,137).…”
Section: Degsmentioning
confidence: 99%
“…1A). In DegS, a trimeric DegP paralog, the H198P mutation results in exactly this phenotype by stabilizing the active conformation of the oxyanion hole (Sohn and Sauer 2009;Sohn et al 2010). Modeling suggested that the homologous R207P mutation in DegP could also stabilize the active conformation, and thus we constructed and purified DegP R207P for biochemical characterization.…”
Section: A Mutation That Stabilizes Active Degpmentioning
confidence: 99%
“…Several observations seem inconsistent with this model. For example, there are no conserved interactions between OMP peptides and the L3 loop in multiple crystal structures, and DegS ΔPDZ has robust OMP-independent proteolytic activity (10,12,14). A second model posits that OMP-peptide binding destabilizes or breaks autoinhibitory contacts mediated by the L3 loop (8,12).…”
mentioning
confidence: 99%
“…The most activating OMP peptide (YYF) increases DegS activity ∼1,000-fold, although other peptides activate to lesser extents because they bind active DegS less tightly or inactive DegS more tightly (8). Activation involves the rearrangement of a network of conserved residues at each subunit interface as well as the formation of a functional oxyanion hole at each catalytic site (6,10,11).…”
mentioning
confidence: 99%